SIRT1 in astrocytes regulates glucose metabolism and reproductive function - Choi, Irene (2019)
Sirtuin 1 (Sirt1) is an NAD-dependent class III deacetylase that functions as a cellular energy sensor. In addition to its well-characterized effects in peripheral tissues, evidence suggests that SIRT1 in neurons plays a role in the central regulation of energy balance and reproduction, but no studies have addressed the contribution of astrocytes. We show here that overexpression of SIRT1 in astrocytes causes markedly increased food intake, body weight gain, and glucose intolerance, but expression of a deacetylase-deficient SIRT1 mutant decreases food intake and body weight and improves glucose tolerance, particularly in female mice. Paradoxically, the effect of these SIRT1 mutants on insulin tolerance was reversed, with overexpression showing greater insulin sensitivity. The mice overexpressing SIRT1 were more active, generated more heat, and had elevated oxygen consumption, possibly in compensation for the increased food intake. The female overexpressing mice were also more sensitive to diet-induced obesity. Reproductively, the mice expressing the deacetylase-deficient SIRT1 mutant had impaired estrous cycles, decreased LH surges, and fewer corpora lutea, indicating decreased ovulation. The GnRH neurons were responsive to kisspeptin stimulation, but hypothalamic expression of Kiss1 was reduced in the mutant mice. Our results showed that SIRT1 signaling in astrocytes can contribute to metabolic and reproductive regulation independent of SIRT1 effects in neurons.